2020
DOI: 10.1111/ppl.13199
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a defense‐responsive bulnesol/elemol synthase from potato

Abstract: Terpene synthases (TPSs) produce a variety of terpenoids that play numerous functional roles in primary and secondary metabolism, as well as in ecological interactions. Here, we report the functional characterization of an inducible potato TPS gene encoding bulnesol/elemol synthase (StBUS/ELS). The expression of StBUS/ELS in potato leaves was significantly induced in response to both bacterial (Pseudomonas syringae) and fungal (Alternaria solani) infection as well as methyl jasmonate treatment, indicating its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It encoded a sesquiterpene synthase (StBUS/ELS) forming bulnesol/elemol and in planta results indicated that StBUS/ELS could have a direct role in providing tolerance against bacterial and fungal pathogens in potato (Dwivedi et al., 2021). During the course of our previous work, we identified another TPS belonging to the TPS‐a clade (StTPS18 , accession number MF997578) that showed highly induced expression in response to only bacterial ( P. syringae) but not fungal ( A. solani ) inoculation (Figure S1 and Table S1–S2) (Dwivedi et al., 2021). Reverse transcriptase quantitative polymerase chain reaction (RT‐qPCR) analysis showed that StTPS18 exhibited a similar pattern of induction in response to both avirulent and virulent strains of P. syringae (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It encoded a sesquiterpene synthase (StBUS/ELS) forming bulnesol/elemol and in planta results indicated that StBUS/ELS could have a direct role in providing tolerance against bacterial and fungal pathogens in potato (Dwivedi et al., 2021). During the course of our previous work, we identified another TPS belonging to the TPS‐a clade (StTPS18 , accession number MF997578) that showed highly induced expression in response to only bacterial ( P. syringae) but not fungal ( A. solani ) inoculation (Figure S1 and Table S1–S2) (Dwivedi et al., 2021). Reverse transcriptase quantitative polymerase chain reaction (RT‐qPCR) analysis showed that StTPS18 exhibited a similar pattern of induction in response to both avirulent and virulent strains of P. syringae (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a TPS that exhibited induced expression in response to methyl jasmonate (MeJA), and bacterial and fungal inoculations was functionally characterized by our group. It encoded a sesquiterpene synthase (StBUS/ELS) forming bulnesol/elemol and in planta results indicated that StBUS/ELS could have a direct role in providing tolerance against bacterial and fungal pathogens in potato (Dwivedi et al., 2021). During the course of our previous work, we identified another TPS belonging to the TPS‐a clade (StTPS18 , accession number MF997578) that showed highly induced expression in response to only bacterial ( P. syringae) but not fungal ( A. solani ) inoculation (Figure S1 and Table S1–S2) (Dwivedi et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oven temperature was increased at the rate of 3 °C min from 60 °C to 150 °C (ramp-1) with a 10 min isothermal hold at 150 °C, then increased to 300 °C at the rate of 10 °C per min (ramp-2). To analyse at a lower temperature sample was injected into GC at 150 °C inlet temperature with the same parameters (Dwivedi et al 2021). Same samples were analysed in GC-MS with the parameter as described earlier.…”
Section: Methodsmentioning
confidence: 99%
“…Sesquiterpenes are mainly synthesized by the mevalonate (MVA) pathway in plants [29]. The universal precursor, farnesyl diphosphate (FPP), can be converted into different sesquiterpene skeletons by different sesquiterpene synthases (SSs) [30]. Previous studies showed that drought stress changed the content of sesquiterpenes in Ocimum basilicum L. by regulating the expression of key genes encoding enzymes of terpene biosynthesis [31].…”
Section: Introductionmentioning
confidence: 99%